Self-esteem, school performance, and self-efficacy in risky-situation of child-waste pickers in Mandurriao, Iloilo City - Gonzales, Rommel V.
This study sought to find the sels-esteem, school performance, and self-efficacy in risky-situation of child-waste pickers in Mandurriao City Dumpsite. Seventy-four (74) child-waste pickers between the ages of 9-20 years old were purposively chosen to serve as respondents., Two instruments were utilized for this study namely: Rosenberg Self-esteem scale (1965) and Self-efficacy in risky-situation scale developed by the researchers. Results showed that the child-waste pickers in Mandurriao Iloilo City Dumpsite are low performers in school. They have high levels of self-esteem indicating that they are globally satisfied with themselves. Likewise, they are average self-efficacious risk takers however, this does not seem to be related to their positive evaluation toward themselves.